1995
DOI: 10.1016/s0022-5347(01)66859-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual Adjustment of Men Who Underwent Hypospadias Repair: Norm-Related Study

Abstract: The majority of hypospadias patients experienced a normal adult sex life. They were reluctant to seek advice for problems. We recommend followup of patients through adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
49
3
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(67 citation statements)
references
References 11 publications
11
49
3
4
Order By: Relevance
“…6,11,12 Further, the low positive genital appraisal may explain their apparently delayed sexual debut, as suggested by Mureau and colleagues. 4,5 Two of our respondents who provided comments corroborated this suggestion by indicating that anxiety over the appearance of their penis had delayed their first sexual experience.…”
Section: Long-term Follow-up Questionnaire Findingssupporting
confidence: 59%
See 4 more Smart Citations
“…6,11,12 Further, the low positive genital appraisal may explain their apparently delayed sexual debut, as suggested by Mureau and colleagues. 4,5 Two of our respondents who provided comments corroborated this suggestion by indicating that anxiety over the appearance of their penis had delayed their first sexual experience.…”
Section: Long-term Follow-up Questionnaire Findingssupporting
confidence: 59%
“…6,8,11 Multiple studies have demonstrated that those with hypospadias have delayed sexual milestones (emotional intimacy, physical intimacy and sexual intercourse). 4,5,7,10,23,24 However, they do not appear to differ significantly from normal men in terms of sexual functioning (erection quality, ejaculation, satisfaction and pain). 4,8,10 These findings also appear to be reflected in our study, in which all but 1 respondent denied difficulty or pain with sexual intercourse or ejaculation and most (15/28, with 6 others being "neutral") indicated satisfaction with their sexual functioning.…”
Section: Long-term Follow-up Questionnaire Findingsmentioning
confidence: 86%
See 3 more Smart Citations